ANALISIS HARGA JUAL SAPI POTONG DI CV.MITRA AGRO SANGKURIANG - Mihrani, Mihrani (POLITEKNIK LP3I JAKARTA, 2023)
Determining product pricing is a crucial aspect of business operations as it directly affects revenue and profitability. This study aims to analyze the production cost and selling price of beef cattle and examine the profit margin above production costs based on the established selling price. The research was conducted at CV Mitra Agro Sangkuriang from March to April 2022. Data collection was done through observation, interviews, and documentation, followed by descriptive quantitative analysis. The research findings indicate that production costs are determined using the full costing method, which includes raw material costs, fixed costs, and variable costs. The established selling price is competitively priced in the market. The average selling price per head of beef cattle is Rp 24,748,200, resulting in a total selling price of Rp 150,729,714,000. Profit margins vary, with the lowest price at Rp 5,680,546 per head in September 2021 and the highest price at Rp 7,242,728 in December 2020. This study provides insights into the pricing strategy of beef cattle at CV Mitra Agro Sangkuriang and its impact on profitability.Key words: Beef Cattle, Production Costs, Selling Prices.